Analysis on meso-damage processes in concrete by X-ray computed tomographic scanning techniques based on divisional zones. (July 2019) - Tian, Wei; Han, Nv
Highlights: X-Ray Computed Tomography analysis in concrete are conducted. The Damage-fracture divisional zone theory is proposed. The thresholds in divisional zones are determined and divisional areas are described. The divisional zones theory using in the deteriorated of concrete is feasible. Abstract: Concrete damage characteristics were investigated by X-ray computed tomography (CT) under uniaxial compression. CT imaging was performed to study concrete crack generation, propagation, coalescence, and failure under uniaxial compression. A damage-fracture divisional zone theory was proposed to quantitatively analyze the damage evolution of concrete by CT. The criteria of the divisional zones based on CT images were determined to define the safety, damage, and damage-fracture zones of a concrete specimen. The different region damage evolutions were revealed and analyzed, which lead to descriptions of concrete deterioration mechanisms.